2012
DOI: 10.1111/j.1600-051x.2012.01935.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between the insulin‐like growth factor axis in serum and periodontitis in the Study of Health in Pomerania: an exploratory study

Abstract: Low serum IGFBP-3 levels might be associated with higher levels of periodontal disease. Neither serum IGF-I nor IGF-I/IGFBP-3 ratios were associated with periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…This decrease may be part of a general suppression of endocrine and energy pathways as a consequence of aging [70]. It was also found in SHIP data that low values of an IGF binding protein, IGFBP-3, were associated with increased levels of periodontitis [71]. Moreover, a protective role of IGF-1 was suggested for vascular aging [72].…”
Section: Discussionmentioning
confidence: 99%
“…This decrease may be part of a general suppression of endocrine and energy pathways as a consequence of aging [70]. It was also found in SHIP data that low values of an IGF binding protein, IGFBP-3, were associated with increased levels of periodontitis [71]. Moreover, a protective role of IGF-1 was suggested for vascular aging [72].…”
Section: Discussionmentioning
confidence: 99%
“…Over 90% of IGF-I is bound to IGF binding protein-3 (IGFBP-3) [9]. IGFBP-3 is also found to be increased in patients with acromegaly [3, 10]. Free serum IGF-I is considered the biologically active form of IGF-I [11].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that high IGFBP-3 levels are associated with less periodontal disease in the general population [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Decreasing insulin-like growth factor 1 (IGF-1) binding proteins are associated with variable tissue outcomes, ranging from periodontal attachment loss to decreased IGF-1. (37) IGF-1 has been shown to be significantly underexpressed in periodontitis lesions compared to healthy periodontal sites. (38) MMP-9 is a well-established inflammatory marker in periodontitis; elevated expression of MMP-9 was demonstrated in close relationship to chronic periodontal disease.…”
Section: Discussionmentioning
confidence: 98%
“…Odontogenic ameloblast‐associated protein has been shown to mediate junctional epithelial attachment to teeth, is present in a healthy periodontium, and is absent in the pathologic periodontitis pocket as was created in ExP. Decreasing insulin‐like growth factor 1 (IGF‐1) binding proteins are associated with variable tissue outcomes, ranging from periodontal attachment loss to decreased IGF‐1 . IGF‐1 has been shown to be significantly underexpressed in periodontitis lesions compared to healthy periodontal sites …”
Section: Discussionmentioning
confidence: 99%